Ethanolamine-assisted synthesis of size-controlled indium tin oxide nanoinks for low temperature solution deposited transparent conductive films. Issue 43 (14th October 2015) - Chen, Zheng; Qin, Xichao; Zhou, Teng; Wu, Xinzhou; Shao, Shuangshuang; Xie, Meilan; Cui, Zheng
Abstract : ITO inks are synthesized by the addition of different concentrations of ethanolamine in reactions for low resistivity high quality films, cooperating with a water washing in film preparation. Abstract : Highly conductive indium tin oxide (ITO) nanocrystals and inks have been synthesized by solvothermal dehydration condensation of metal hydroxide in combination with in situ ethanolamine capping. It is found that the addition of ethanolamine can effectively reduce the size of nanocrystals and chemically modify their surfaces. The synthesized ITO nanocrystals can be well dispersed in ethanol with high solid content and the suspension is stable for days. Such a small-molecule capped ITO suspension has been used as a conductive ink to make transparent conductive films by spin coating. Furthermore, a water washing step has been introduced in the ITO film preparation process to improve their conductivity, resulting in a low resistivity of 8.9 × 10 −3 Ω cm after 2 hour annealing at 300 °C in a mixed Ar and H2 atmosphere.